Creating opportunities in a challenging environment: experiential crisis learning behaviour of tourism SMEs in Sri Lanka - Kalutara Koralalage Nilanthi Britto Adikaram; Hapugoda Achchi Kankanamge Nadee Sheresha Surangi (Cogent Business & Management, 2024)
This study considers the opportunity creation aspect of SMEs rather than taking a general view of threats posed by crises. Thus, this phenomenological study investigates how and what Small and Medium Enterprises (SMEs) have learned from previous crisis experiences to create knowledge within SMEs and apply such knowledge to deal with future crisis events. Using the Social Constructivist approach, the researchers investigate the experiential crisis learning behaviour of SMEs. Hence, it purposively selected 19 tourism SMEs to extract information about their crisis learning behaviour through their lived experiences. The real-time data collected during the height of the Covid-19 pandemic will likely prove highly influential and valuable for the study. The findings of the study reveal that SMEs have improved and applied knowledge successfully by adopting several strategic approaches, namely bricolage, financial management, market diversification, proactive posture, and developing solid business with embedded knowledge. These findings prompted the creation of a model of the SME's experiential crisis learning process that could be served as a benchmark.
Keywords: 650; crisis; experiential learning; sMe; tourism; phenomenology; social constructivism